Conditional Cash Transfer (CCT) and national development in Nigeria: emerging pitfalls and pathways to results - Chima Paul (Journal of Enterprise and Development (JED), 2022)
Purpose — This paper addresses the pitfalls in conditional cash transfer in Nigeria and suggested the best practices to enhance the performance of the social policy instrument in Nigeria.Research method — This paper is library research which evaluates the issue at stake using documentary evidence from secondary means of data collection such as textbooks, journal articles, newspapers and so on.Result — The paper found that conditional cash transfer in Nigeria is characterized with several anomalies. These among others identified in the study include diversion of funds by the beneficiaries for purposes other than investing in what it was originally meant for, the improper definition of exit and entry period (a period of one year is allowed in Nigeria) and this translates to nothing meaningful. It was found that beneficiaries are randomly selected in Nigeria, thus leading to obvious errors of exclusion and inclusion.Recommendations — This paper recommends among others that a formidable system of entry and exit rules, monitoring and evaluation mechanism, cash disbursement mechanism as well as grievance redress mechanism be put in place as practised in other climes. These systems will no doubt enhance the service quality, value for money, transparency and accountability of the social protection policy, culminating in the social-economic development of the Nigerian states.